THE PREVALENCE AND FACTORS ASSOCIATED WITH THE USE OF PSYCHOPHARMACEUTICALS, SPECIFICALLY ANXIOLYTICS AND ANTIDEPRESSANTS, AMONG NEWLY GRADUATED PHARMACISTS IN THE FIRST THREE YEARS OF CAREER - Ferreira de Oliveira, Lincoln; Martins Franca, Angélica; Rocha de Souza, Gislaine; Persona Reinaldo, Ricardo (Health and Society, 2024)
This course completion work aims to explore the prevalence and factors associated with the use of psychopharmaceuticals, specifically anxiolytics and antidepressants, among recently graduated pharmacists in the first three years of career. The research seeks to answer the following question: What is the prevalence of the use of psychopharmaceuticals by pharmaceutical professionals in the first three years of active entry into the job market? The literature review will address the challenges faced by pharmacists at the beginning of career, including stress, excessive workload and the process of adaptation to the professional environment. These factors can contribute to the increase in the use of psychopharmaceuticals as a strategy to deal with the pressures and demands of the new profession. The results of this study are expected to provide valuable insights on the mental health of early career pharmacists and help develop strategies and policies to support these professionals in their transition to the job market.